Spiroplasma eriocheiris Adhesin-Like Protein (ALP) Interacts with Epidermal Growth Factor (EGF) Domain Proteins to Facilitate Infection - Hou, Libo; Liu, Yuhan; Gao, Qi; Xu, Xuechuan; Ning, Mingxiao; Bi, Jingxiu; Liu, Hui; Liu, Min; Gu, Wei; Wang, Wen; Meng, Qingguo (Frontiers in Cellular and Infection Microbiology, 2017)
Abstract Spiroplasma eriocheiris is a novel pathogen found in recent years, causing the tremor disease (TD) of Chinese mitten crab Eriocheir sinensis. Like Spiroplasma mirum, S. eriocheiris infects the newborn mouse (adult mice are not infected) and can cause cataract. Adhesion-related protein is an important protein involved in the interaction between pathogen and host. In this study, the Adhesin-like Protein (ALP) of S. eriocheiris was detected on its outer membrane by using immune electron microscopy, and was found to be involved in the bacterium’s infection of mouse embryo fibroblasts (3T6-Swiss albino). Yeast two-hybrid analysis demonstrated that ALP interacts with a diverse group of mouse proteins. The interactions between recombinant partial fibulin7 (FBLN7; (including two epidermal growth factor [EGF] domains) and ALP were confirmed by Far-western blotting and colocalization. We syntheticed the domains of FBLN7 (EGF domain: amino acids 136-172 and complement control protein [CCP] domain:81-134 amino acids), and demonstrated that only EGF domain of FBLN7 can interact with ALP. Because the EGF domain has high degree of similarity to EGF, it can activate the downstream EGFR signaling pathway, in key site amino acids. The EGFR pathway in 3T6 cells was restrained after rALP stimulation resulting from competitive binding of ALP to EGF. The unborn mouse, newborn mouse, and the adult mouse with cataract have a small amount of expressed FBLN7; however, none was detected in the brain and very little expression was seen in the eye of normal adult mice. In short, ALP as a S. eriocheiris surface protein, is critical for infection and further supports the role of ALP in S. eriocheiris infection by competitive effection of the EGF/EGFR axis of the target cells.